Is Early Marriage a Problem in Indonesia? Maqāṣid Al-Sharī‘ah, Economic and Quadruple Helix Analysis - Hidayat, Yusup; Machmud, Aris; Sadino, Sadino; Lutfi, Anas; Maguchu, Prosper (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2024)
Early marriage is a contributing factor to low levels of health, education, and family welfare. Early marriage is a worldwide occurrence that warrants the attention of all stakeholders, including UNICEF. The objective of this study is to address the issue of early marriage in Indonesia by employing the quadruple helix approach and doing legal and economic analysis to effectively reduce the prevalence of early marriages. The author employed a type of normative juridical study that incorporated both national law and the Islamic legal method approach known as maqāṣid al-sharī‘ah. This was done by utilizing the quadruple helix and economic analysis of law (EAL) theory. Ultimately, early marriage is influenced by ineffective regulations as well as cultural, economic, and educational factors. To address this issue, it is crucial to establish a strong collaboration between academics, businesses, government, and society. Additionally, raising awareness among the public about the benefits of delaying marriage until the appropriate age can contribute to the well-being of couples, families, and society as a whole. This approach can also incentivize the community by facilitating access to education, the economy, and healthcare and addressing issues such as stunting.